Some aspects of morphophysiography of Labeo calbasu (Ham.) from Rana Pratap Sagar reservoir, Rajasthan - Choudhary, C S; Sharma, L L; Sharma, S K; Saini, V P (Indian Journal of Fisheries, 2011)
Length-weight relationship for any fishspecies gives its performance and well beingin relation to habitat and helps in monitoringthe status offish stock for obtaining optimumyield. These relationships may vary from timeto time in the same water body due to alterationsin water quality and fish stocks. Studieson length-weight relationships and conditionfactors have widely attracted the attention offishery biologists O^ao and Rao 1972, Kumar1988). However, on Rajasthan waters suchresearches are comparatively meagre